Effect of Bioreductant–Precursor Ratio on the Physical Characteristics of Silver Nanoparticles Synthesized via Green Synthesis Using Lemongrass (Cymbopogon citratus) and Betel Leaf (Piper betle L.) Extracts - Andini Khairi Alena; Riri Jonuarti; Leni Aziyus Fitri; Eka Susanti (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Green synthesis of silver nanoparticles (AgNPs) using plant extracts offers an environmentally sustainable alternative to conventional synthesis methods; however, the influence of the bioreductant-to-precursor ratio in dual-bioreductant systems on the physical characteristics of AgNPs remains insufficiently understood. This study aimed to determine the effect of different bioreductant-to-precursor ratios on the physical characteristics of AgNPs synthesized using combined lemongrass (Cymbopogon citratus) and betel leaf (Piper betle L.) extracts. AgNPs were synthesized at bioreductant-to-precursor ratios of 1:9, 2:8, and 3:7 and characterized using UV–Visible spectroscopy, X-ray diffraction (XRD), and particle size analysis (PSA). UV–Visible spectroscopy confirmed the formation of AgNPs through the appearance of surface plasmon resonance peaks across all ratio variations. The 1:9 ratio exhibited the strongest optical characteristics, with a maximum absorption wavelength of 423 nm and the highest absorbance value of 2.165. XRD analysis verified the formation of AgNPs with a face-centered cubic crystalline structure and average crystallite sizes ranging from 18.45 to 23.80 nm. PSA results showed hydrodynamic particle diameters ranging from 38.3 to 137.7 nm and polydispersity index values of 0.096–0.306. An integrated evaluation of the characterization results identified the 1:9 ratio as the optimum synthesis condition because it produced the best balance between smaller particle size and higher surface plasmon resonance intensity. Nevertheless, the 2:8 ratio yielded the most homogeneous particle size distribution, as indicated by the lowest polydispersity index. These findings demonstrate that the bioreductant-to-precursor ratio critically influences the optical, structural, and particle-size characteristics of AgNPs. This study contributes to the optimization of environmentally sustainable AgNP synthesis using complementary plant-derived bioreductants.